Students’ Perceptions of English Learning during Teaching Assistance Program in Vocational High School - Nurzila Diah Malatifa; Dewi Sri Kuning (Journal of English Language and Education, 2026)
English plays an important role in vocational education because it supports students’ workplace readiness and future career opportunities. However, previous studies mostly focused on digital media and classroom methods, while studies examining students’ perceptions during teaching assistance programs, in which university students assist classroom instruction, remain limited. This study aimed to analyze students’ perceptions of English learning during the teaching assistance program at SMKN 1 Abung Selatan based on Bimo Walgito’s theory, which includes cognitive, affective, and conative components. This study employed a descriptive quantitative design with a 24-item questionnaire distributed to 33 students of class XI Accounting 2. The instrument was reliable with a Cronbach’s Alpha value of 0.730. The findings showed that students had a very positive perception, with an overall mean score of 4.50 (90.08%). The cognitive component gained the highest score, followed by affective and conative. These results indicate that the program effectively improved students’ understanding, motivation, comfort, and participation in English learning.